Active VLF Transmission Experiments Between the DSX and VPM Spacecraft. Issue 4 (11th April 2022) - Reid, Riley A.; Marshall, Robert A.; Starks, Michael J.; Usanova, Maria E.; Wilson, Gordon R.; Johnston, W. Robert; Sanchez, Jenny C.; Su, Yi‐Jiun; Ginet, Gregory P.; Song, Paul; Galkin, Ivan A.
Abstract: This study presents results from magnetic field line conjunctions between the medium‐Earth orbiting Demonstration and Science Experiments (DSX) satellite and the low‐Earth orbiting (LEO) very low frequencies (VLF) Propagation Mapper (VPM) satellite. DSX transmitted at VLF toward VPM, which was equipped with a single‐axis dipole electric field antenna, when the two spacecraft passed near the same magnetic field line. VPM did not observe DSX signals in any of the 27 attempted conjunction experiments; the goal of this study, therefore, is to explain why DSX signals were not received. Explanations include (a) the predicted power at LEO from DSX transmissions was too low for VPM to observe; (b) VPM's trajectory missed the "spot" of highest intensity due to the focused ray paths reaching LEO; or (c) rays mirrored before reaching VPM. Different combinations of these explanations are found. We present ray‐tracing analysis for each conjunction event to predict the distribution of power and wave normal angles in the vicinity of VPM at LEO altitudes. We find that, for low‐frequency (below 4 kHz) transmissions, nearly all rays mirror before reaching LEO, resulting in low amplitudes at LEO. For mid‐ and high‐frequency transmissions (∼8 and 28 kHz respectively), the power at LEO is above the noise threshold of the VPM receiver (between 0.5  μ V/m and 1  μ V/m). We conclude that the antenna efficiency and plasmasphere model are critical in determining the predicted power at LEO, and are also the two most significant sources of uncertainty that could explain the apparent discrepancy between predicted amplitudes and VPM observations. Plain Language Summary: In this study we present results from transmissions between two near‐Earth spacecraft. The Demonstration and Science Experiments (DSX) satellite transmitted signals at very low radio frequencies (VLF) toward the VLF Propagation Mapper (VPM) satellite when the two satellites passed near the same magnetic field line. VLF broadcasts tend to follow magnetic field lines as they are guided by the plasma in the magnetosphere. This study is important for understanding VLF wave propagation in the near‐Earth space environment. We analyze the data from each experiment and conclude that DSX broadcasts were not observed by VPM. The goal of this paper is to describe our analysis to explain possible reasons for the lack of observation. We perform ray‐tracing, or solving for the paths of the VLF broadcasts, to explain why VPM missed the signals. We conclude that in some cases, the broadcasts mirrored, or reversed direction in the near‐Earth space environment before they were able to reach VPM. In other cases, the ray‐tracing analysis predicts we should have observed the signals. However, we find that the DSX antenna performance and the model of the near‐Earth environment we use in these simulations are significant sources of uncertainty that could explain this discrepancy. Key Points: Results from active conjunction experiments between Demonstration and Science Experiments (DSX) and Very Low Frequency Propagation Mapper are presented Ray‐tracing is performed to investigate the lack of DSX signal observation The effects of the antenna efficiency and plasmasphere model are explored